MODERN BUSINESS TRENDS : HOW INNOVATION DRIVES ECONOMIC GROWTH - Eko Putro Wibowo; Heri Rismayanto; Zakhi Bailatul Nur Avian; Amra Ulvita Azhiin (ADISAM Publisher, 2025)
Innovation has become a key element in the development of modern business trends and plays an important role in driving economic growth around the world. This article examines various forms of innovation—whether in products, services, or processes—and their impact on corporate competitiveness and job creation. By leveraging technological advances, such as artificial intelligence and data analysis, companies can improve operational efficiency and better meet customer needs. Additionally, innovations in business models, such as e-commerce and the sharing economy, have opened up new opportunities for small and medium-sized businesses to participate in global markets. This article also highlights the importance of creating a culture of innovation within organizations as well as supporting government policies that can strengthen the innovation ecosystem. Through this approach, innovation not only provides economic benefits for companies, but also contributes to more inclusive and sustainable social development. innovation that focuses on sustainability and inclusivity can help overcome social and environmental challenges, and promote more equitable economic development. However, to maximize the positive impact of innovation, support from the government and other stakeholders is needed through policies that support research, development and investment in new technologies. Thus, innovation is not only the key to the success of individual companies, but also a key pillar for sustainable and inclusive economic growth in the future.